Volatilomic response to targeted cancer therapy in vitro - Philip K. H. Leung; Innah Kim; Bibek Das; George B. Hanna (Scientific Reports)
Abstract Clinical advancement of novel therapeutics is often hindered by variable patient responses. Therefore, clinically translatable biomarkers of response are urgently required to facilitate precision medicine trials. Endogenous volatile organic compounds (VOCs) can be non-invasively detected in exhaled breath and biofluids and have shown great potential for early cancer detection. Since emerging evidence suggests that cancer-associated VOCs may reflect alterations in the tumour lipidome, we speculated that the response to metabolically active therapies could be monitored through VOC measurement. In this proof-of-concept study, we investigated the lipidomic and volatilomic profiles of mTOR catalytic inhibitors (mTORci)-resistant and -sensitive colorectal cancer cells. Distinct lipid-derived VOC signatures, including upregulated alkenes, aldehydes, and fatty acids were observed in mTORci-resistant cells. These enriched VOCs correlated with phospholipid structure and desaturation positions, suggesting that they may be surrogates of dysregulated lipid metabolism. This novel association between VOCs and drug response establishes a precedent for further investigation into VOC biomarkers of treatment response. VOCs associated with therapy response in vitro need to be targeted in clinical trials to identify biomarkers that could be translated to monitor therapeutic response in a clinical setting.